2017
DOI: 10.1039/c7ra04751g
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of polyphosphoric acid-activated nitroalkanes in oxidative peri-annulations: efficient synthesis of 1,3,6,8-tetraazapyrenes

Abstract: Electrophilically activated nitroalkanes play a dual role in the novel reaction with diaminoperimidines, promoting their oxidative peri-annulation to access tetraazapyrenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…These phosphorylated nitronates tend to react with various carbon-based nucleophiles, for instance electron-rich arenes, allowing for Friedel-Crafts-type C-H functionalization reactions, often with subsequent accompanying rearrangements [21][22][23][24]. Furthermore, it was found that nitrogen-based nucleophiles (6), such as aliphatic amines [25][26][27], anilines [28][29][30][31], or hydrazines [32,33], can be utilized instead of water in a process mechanistically related to the classical Nef reaction [34][35][36]. Employing strategically placed second nucleophilic functionality (carbon or heteroatom-based), the resulting amidinium species (7) can be transformed into a variety of heterocyclic compounds, such as benzoxazoles (8) [23,28] or benzimidazoles (9) [28], perimidines (10) [29], 6,7-dihydro-1H-cyclopenta[gh]perimidines (11) [31], 1,3,4-oxa-di-azoles (12) [32,33], imidazolines (13) [25], 3,4-dihydro-iso-quinolines (14) [27], imidazo [1,5-a]pyridines (15) [26], and [1,2,4]triazolo [4,3-a] It occurred to us that a similar strategy can be applied for the straightforward preparation of 3,4-dihydroquinazolines as well.…”
Section: Resultsmentioning
confidence: 99%
“…These phosphorylated nitronates tend to react with various carbon-based nucleophiles, for instance electron-rich arenes, allowing for Friedel-Crafts-type C-H functionalization reactions, often with subsequent accompanying rearrangements [21][22][23][24]. Furthermore, it was found that nitrogen-based nucleophiles (6), such as aliphatic amines [25][26][27], anilines [28][29][30][31], or hydrazines [32,33], can be utilized instead of water in a process mechanistically related to the classical Nef reaction [34][35][36]. Employing strategically placed second nucleophilic functionality (carbon or heteroatom-based), the resulting amidinium species (7) can be transformed into a variety of heterocyclic compounds, such as benzoxazoles (8) [23,28] or benzimidazoles (9) [28], perimidines (10) [29], 6,7-dihydro-1H-cyclopenta[gh]perimidines (11) [31], 1,3,4-oxa-di-azoles (12) [32,33], imidazolines (13) [25], 3,4-dihydro-iso-quinolines (14) [27], imidazo [1,5-a]pyridines (15) [26], and [1,2,4]triazolo [4,3-a] It occurred to us that a similar strategy can be applied for the straightforward preparation of 3,4-dihydroquinazolines as well.…”
Section: Resultsmentioning
confidence: 99%
“…As we previously reported, a highly electrophilic phosphorylated nitronate species A is generated upon the interactions between nitroalkanes 1 and polyphosphoric acid (PPA) ( Scheme 1 ). These entities readily react with amines B to afford amidinium intermediates C , which can be used for the highly efficient assembly of imidazoles or oxazoles ( D ) [ 20 , 21 ], as well as imidazolines [ 22 ] and other nitrogen-based heterocycles [ 23 , 24 ]. Furthermore, the reaction with 2-hydrazinylpyridines H enacts formation of the corresponding (hydrazineyl)alkaniminium species I , which was found to undergo intramolecular cyclocondensations to obtain 1,2,4-triazolo[4,3- a ]pyridines ( J ) ( Scheme 1 ) [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was also discovered that the nucleophilic amines 3 can be successfully employed in this type of transformations as well, providing the amidinium intermediates 4 , which are susceptible to a variety of subsequent cyclizations. This approach opens up a novel avenue by which to access the benzoxazoles 5 [ 40 ], benzimidazoles 6 [ 40 41 ], diazines 7 [ 42 43 ], or imidazolines 8 ( Scheme 1 ) [ 44 ]. We have also shown that a nucleophilic attack on the phosphorylated nitronate species 2 can be carried out with the participation of N -acylhydrazides or thiosemicarbazides to afford the 1,3,4-oxadiazoles 9 [ 45 ] and the 1,3,4-thiadiazoles 10 [ 46 ], respectively ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%